Elevated seawater temperature disrupts the microbiome of an ecologically important bioeroding sponge. Issue 8 (31st March 2018) - Ramsby, Blake D.; Hoogenboom, Mia O.; Whalan, Steve; Webster, Nicole S.
Abstract: Bioeroding sponges break down calcium carbonate substratum, including coral skeleton, and their capacity for reef erosion is expected to increase in warmer and more acidic oceans. However, elevated temperature can disrupt the functionally important microbial symbionts of some sponge species, often with adverse consequences for host health. Here, we provide the first detailed description of the microbial community of the bioeroding sponge Cliona orientalis and assess how the community responds to seawater temperatures incrementally increasing from 23°C to 32°C. The microbiome, identified using 16S rRNA gene sequencing, was dominated by Alphaproteobacteria, including a single operational taxonomic unit (OTU; Rhodothalassium sp.) that represented 21% of all sequences. The "core" microbial community (taxa present in >80% of samples) included putative nitrogen fixers and ammonia oxidizers, suggesting that symbiotic nitrogen metabolism may be a key function of the C. orientalis holobiont. The C. orientalis microbiome was generally stable at temperatures up to 27°C; however, a community shift occurred at 29°C, including changes in the relative abundance and turnover of microbial OTUs. Notably, this microbial shift occurred at a lower temperature than the 32°C threshold that induced sponge bleaching, indicating that changes in the microbiome may play a role in the destabilization of the C. orientalis holobiont. C. orientalis failed to regain Symbiodinium or restore its baseline microbial community following bleaching, suggesting that the sponge has limited ability to recover from extreme thermal exposure, at least under aquarium conditions.